Vidas exemplares : um estudo dos perfis biográficos publicados na Revista Veja entre 1990 e 2020 - Carmo, Aparecido Santos do (2022)
The present work aims to identify the values and social norms presented through exemplary figures in the biographical profiles published by Veja magazine between 1990 and 2020. The choice of Veja is because this is the oldest weekly publication in circulation and the one that has the highest number of copies sold. Based on Douglas Kellner's (2001) definitions of “media culture”, this work identifies the criteria taken into account to define the characters that are worthy of a biographical profile in the magazines of wide circulation in the country and which are the most popular types. common to appear in these narratives. We take into account that all narratives bring with them an ideology, a moral background that is presented to the audience as being positive or negative. To take this proposal forward, it was necessary to build a representative sample of the whole of the publications, for this we used the constructed year method, in addition to using the Discursive Textual Analysis as a methodology, according to Moraes and Galiazzi (2016). Among the results achieved, it was possible to understand Veja magazine as a vehicle that reproduces in its pages the interests of a minority portion of the population, marked by political liberalism.